The Lives of Jessie Sampter - Imhoff, Sarah (Duke University Press, 2022)
Sarah Imhoff tells the story of the queer, disabled, Zionist writer Jessie Sampter (1883-1938), whose body and life did not match typical Zionist ideals and serves as an example of the complex relationships between the body, queerness, disability, religion, and nationalism.